Plasma Proteomic Analysis of Simian Immunodeficiency Virus Infection of Rhesus Macaques - Wiederin, Jayme L. (2010)
Lentiviral replication in its target cells affects a delicate balance between cellular co-factors required for virus propagation and immunoregulation for host defense. To better elucidate cellular proteins linked to viral infection we tested plasma from rhesus macaques infected with the simian immunodeficiency viral strain SIVsmm9, prior to, 10 days (acute) and 49 weeks (chronic) after viral infection. Changes in plasma protein content were measured by quantitative mass spectrometry by isobaric Tags for Absolute and Relative Quantitation (iTRAQ) methods. An 81 and 232% increase in SERPINA1 was seen during acute and chronic infection, respectively. Interestingly, gelsolin, vitamin D binding protein and histidine rich glycoprotein were decreased by 45% in acute conditions but returned to baseline during chronic infection. When compared to uninfected controls, a 48–103% increase in leucine rich alpha 2-glycoprotein, vitronectin and ceruloplasmin was observed during chronic viral infection. Observed changes in plasma proteins expression likely represent a compensatory host response to persistent viral infection.